S'il vous plaît aidez moi!!
Factorisez les expressions suivantes : (J'y comprends rien!)
D(x)=(2x+3)(x-7)+(2x+3)(-4x+5)
E(x)=4x²-4x+1
F(x)=(x-1)(2x+4)-(x-1)(x+5)+2(x-1)
G(x)=9(x+1)²-16
H(x)=(x+3)²-3(x+3)(-2x+4)

Merci

1

Réponses

2014-09-28T12:52:05+02:00
D(x)=(2x+3)(x-7)+(2x+3)(-4x+5) = (2x+3)(x-7-4x+5) = (2x+3)(-3x-2)
E(x)=4x²-4x+1 = (2x)² - 2.2x+1² = (2x-1)²
F(x)=(x-1)(2x+4)-(x-1)(x+5)+2(x-1) = (x-1)(2x+4x-(x+5)+2) = (x-1)(2x+4x-x-5+2) = (x-1)(5x-3)
 
G(x)=9(x+1)²-16 = (3(x+1))² - 4² = (3(x+1)+4)(3(x+1)-4)
H(x)=(x+3)²-3(x+3)(-2x+4) = (x+3)(x+3-3(-2x+4)) =  (x+3)(x+3+6x-12) =  (x+3)(9x-9)